The relationship between periodontitis and tooth decay in juvenile diabetes mellitus cases and in healthy children - (:unkn) unknown (My University, 1990)
Children diagnosed as having juvenile diabetes mellitus have been compared with healthy children of the same age, with respect to decayed, filled primary teeth (df), decayed, missing, filled permanent teeth (DMF), Gingival index (GI), Periodontal index (PI), Oral hygiene index (OHI). These parameters have been evaluated according to WHO criteria. Corresponding parameters have been statistically evaluated. When experimental and control groups were compared statistically, a highly significant difference was seen between df and DMF indexes of diabetic and healthy children. In the periodontal evaluation, a significant difference was found in the gingival index, but no such significance was seen in the periodontal index. From the results of this study it can be seen that children with juvenile diabetes mellitus had less caries incidence compared with the control group. Even though gingival destruction had already started in this study group, intense periodontal damage was not observed at this particular age level.
Keywords: Female; Humans; Adolescent; Male; Child; Dental Caries; DMF Index; Diabetes Mellitus, Type 1; Periodontal Index; Periodontitis